Nonlinear dynamical performance of microsize piezoelectric bridge-type energy harvesters based upon strain gradient-based meshless collocation approach. (June 2023) - Alshenawy, Reda; Sahmani, Saeid; Safaei, Babak; Elmoghazy, Yasser; Al-Alwan, Ali; Sobhy, Mohammed
Abstract: In the current exploration, the size-dependent nonlinear dynamical performance of piezoelectric bridge-type energy harvesters at microscale is analyzed. The proposed microbeam-type energy harvesters are made of a lightweight agglomerated nanocomposite polymeric passive bulk reinforced with carbon nanotubes (CNTs) and integrated with piezoelectric facesheets. In order to perform a highly accurate analysis, the modified strain gradient continuum elasticity is adopted within the framework of the quasi-3D beam theory incorporating various microstructural-dependent strain gradient tensors. Thereafter, the size-dependent nonlinear coupled electromechanical differential equations are solved numerically via employing the meshless collocation technique using a combination of the radial basis and polynomial basis functions to avoid any possible singularity. It is demonstrated that by increasing the amount of CNTs inside clusters, the effect of strain gradient tensors on the reduction in the value of induced deflection in microsized energy harvester decreases from 25.57% to 22.65% for simply supported boundary conditions, and from 33.96% to 31.56% for clamped boundary conditions. Also, the average of achieved voltage by the microsized energy harvesters increases from 245.1  mv to 262.8  mv for simply supported boundary conditions, and from 79.5  mv to 96.7  mv for clamped boundary conditions.